How to Increase the Accountability of Cash Waqf Linked Sukuk: Maqāṣid Asy-Syarī‘ah Approach - Arianty, Erny; Nafis, M. Cholil; Ghoni, Abdul (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2023)
Abstract. One of the causes of Cash Waqf Linked Sukuk fundraising that has not reached the expected value is the low implementation of accountability. This study aims to analyze the strategy that has the most effect on increasing CWLS accountability with the Maqāṣid Asy-syarī'ah approach. The method uses the theme approach and ANP. The results show that the strategies needed include program-related competency development, professional management, accounting and reporting, and technology. Another strategy is information management which is conveyed to the Wakif. The implications contribute to stakeholders in coordinating plans and initial steps to implement this strategy. Abstrak. Salah satu penyebab penggalangan dana Cash Waqf Linked Sukuk belum mencapai nilai yang diharapkan adalah rendahnya implementasi akuntabilitas. Penelitian ini bertujuan untuk menganalisis strategi yang paling berpengaruh meningkatkan akuntabilitas CWLS dengan pendekatan Maqāṣid Asy-syarī‘ah. Metode menggunakan pendekatan tema dan ANP. Hasil menunjukkan strategi yang dibutuhkan meliputi pengembangan kompetensi terkait program, manajemen profesional, akuntansi dan pelaporan, serta teknologi dan strategi pengaturan informasi yang disampaikan kepada wakif. Implikasi penelitian memberikan kontribusi bagi pemangku kepentingan dalam mengkoordinasikan rencana dan langkah awal untuk menerapkan strategi ini.